First-principles study of the structure, magnetism, and electronic properties of the all-Heusler alloy Co2MnGe/CoTiMnGe(100) heterojunction - He, Jianqiao; Huang, Haishen; Wu, Bo; Shen, Guangxian; Zhou, Tingyan; Gu, Yuxin; Wen, Lin; Zhang, Qingqing (Frontiers in Chemistry, 2024)
Based on first-principles calculations in density functional theory, we systematically investigate the possible interface structure, magnetism, and electronic properties in the all-Heusler alloy Co2MnGe/CoTiMnGe(100) heterojunction. The calculation indicates that Co2MnGe Heusler alloy is a half-metal with a magnetic moment of 4.97 μB. CoTiMnGe is a narrow-band-gap semiconductor and may act as an ultra-sensitive photocatalyst. We can not find an "ideal" spin-polarization of 100% in the CoCo-termination and the MnGe-termination. Due to the fact that interface interaction, the direct magnetic hybridization or indirect RKKY exchange will be weakened, leading to an increase of atomic magnetic moment of the interfacial layer. For eight possible heterojunction structures, the half-metallic gaps in Co2MnGe bulk have been destroyed by the inevitable interface states. The spinpolarization value of 94.31% in CoCo-TiGe-B heterojunction reveals that it is the most stable structure. It is feasible to search for high-performance MTJ by artificially constructing suitable all-Heusler alloy heterojunctions.